The Impact of the Coastal Embankment Construction on Social Changes in the Community - Mursyidin; Zuhilmi; Chalid, Ibrahim; Hafinda, Tengku (International Journal of Education, Language, and Social Science, 2023)
The study investigated the socio-economic impact of embankment construction around Ujong Kareung beach on the community of Gampong Suak Indrapuri, West Aceh District. Conducted as a qualitative descriptive research, the study focused on fishermen, traders, and fish cultivators in the area. Data was gathered through interviews, observation, and documentation.The results indicated two fundamental changes within the community. Firstly, embankment construction diversified livelihoods along the coast, encompassing activities such as fishing, shrimp cultivation, trade, and anchovy and salted fish cultivation. Secondly, there were notable shifts in income among the three livelihood types. Fishermen and traders experienced a decrease in monthly income, while fish cultivators witnessed an increase. From an ecotourism perspective, the beach barrier construction influenced various aspects, including the growth of cooperation and collaboration within the community. Additionally, it spurred high participation in developing and managing ecotourism at Suak Indra Puri Beach, leading to the establishment of new culinary tourism spots. The area became an innovative pilot village for managing tourism products in Gampong Suak Indra Puri. However, the study identified challenges, such as changing attitudes within the community from initial enthusiasm to later pessimism and apathy. Internal conflicts between communities and the gampong government emerged, contributing to apathy, and family modernization led to strained relationships among family members. Overall, the research shed light on the complex socio-economic dynamics resulting from embankment construction and its broader implications on community life.